Agricultural Information Need of Smallholder Farmers in Chitwan District, Nepal - Mishra, B.P.; Bhatta, S. (International Journal of Applied Sciences and Biotechnology, 2021)
Agricultural information is very essential for smallholder farmers to increase farm production and productivity. However, there is no proper access to accurate and adequate agricultural information to smallholder farmers. This paper attempts to identify the existing agricultural information source and the agricultural information need of the smallholder farmers along with usefulness of the provided agricultural information. Household level data were obtained from four wards of Bharatpur metropolitan of Chitwan district during 2019. The result showed agrovet shops as most common source of agricultural information for smallholder farmers. The most needed agricultural information was about input market and prices followed by disease and pest control. Moderately useful agricultural information was provided to smallholder farmers. Findings of this research suggest that context specific agricultural information should be provided through the existing channels to the smallholder farmers. Int. J. Appl. Sci. Biotechnol. Vol 9(2): 94-97.